2008
DOI: 10.1159/000114858
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Expressed Genes Are Missing in Familial X-Linked Kallmann Syndrome due to Two Large Different Deletions in Daughter’s X Chromosomes

Abstract: Background: X-linked Kallmann syndrome (KS) is caused mainly by point mutations, in the KAL1 gene. Large deletions >1 Mb are rare events in the human population and commonly result in contiguous gene syndromes. Methods: A search for the mutation causing KS carried out on two pairs of first-degree cousins of 2 sisters. Results: Two different apparently independent deletions were found. The deleted sequences encompass the KAL1 gene and four known additional genes exclusively expressed in testis. Two of these gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Notably, the breakpoint-flanking regions of this deletion contained Alu repeats but not palindromes or non-B motifs. In this regard, Hershkovitz et al [2008] reported that the NHEJ-induced deletion in their cases was accompanied by L1 repeats. Thus, MMBIR and NHEJ at Xp22.31 could be facilitated by repeat sequences independently of other rearrangement-inducing DNA features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the breakpoint-flanking regions of this deletion contained Alu repeats but not palindromes or non-B motifs. In this regard, Hershkovitz et al [2008] reported that the NHEJ-induced deletion in their cases was accompanied by L1 repeats. Thus, MMBIR and NHEJ at Xp22.31 could be facilitated by repeat sequences independently of other rearrangement-inducing DNA features.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, NAHR is unlikely to be involved in other Xp22.31 microdeletions that are not associated with repetitive sequences. In 2008, Hershkovitz et al characterized the genomic structures of 2 ANOS1 -containing microdeletions harbored by members of the same family [Hershkovitz et al, 2008]. The breakpoints of these deletions shared no homology and had short nucleotide stretches at the fusion junctions, indicating that nonhomologous end-joining (NHEJ) underlies these copy number variations (CNVs) [Hershkovitz et al, 2008].…”
mentioning
confidence: 99%